Pengaruh Promosi Kesehatan Menggunakan Media Video Terhadap Pengetahuan Vaksin Covid-19 Pada Anggota Saka Bakti Husada Kota Bandung Tahun 2021 - Juju Juhaeriah; Dedi Nurhanes (LPPM Stikes Jenderal Achmad Yani Cimahi, 2022)
Background : Promotional media through video is a very good way of providing information because video media can be accessed by more than one human sense, especially hearing and sight. Video media can make people focus on promotional materials because of the movement that makes the eyes focus on looking at the movement rather than just still images that tend to be monotonous. With the existence of video media in health promotion, it is hoped that Saka Bakti Husada members will be able to understand and learn about COVID-19 and the COVID-19 Vaccine. A member of Saka Bakti Husada, is one of the health cadres and agents of change in the city of Bandung. The purpose of this study was to determine the effect of health promotion using video media on knowledge of the COVID-19 Vaccine on members of Saka Bakti Husada Bandung City in 2021. Method : The research design used was pre-experimental with a one group pretest-posttest design. The sample consisted of 50 members of Saka Bakti Husada Bandung City. The sampling technique used was total sampling. The research data was collected using a questionnaire. Data analysis used univariate and bivariate paired t test non parametic Wilcoxon at a significant level of 5%. Result and Conslusion: The results showed the level of knowledge before watching the Covid-19 Vaccine video in the form of good knowledge of 2%, sufficient knowledge of 42%, and 56.0% less knowledge, and after watching the Covid-19 Vaccine video there was an increase in the level of knowledge to 80% good knowledge and sufficient knowledge of 20 %. The results of the non-parametic Wilcoxon paired t test, showed that the value of p = 0.000 < 0.005 means that there is a significant difference in the average knowledge before and after being given health promotion.